The New Normal: Navigating Cyber Security Challenges in Remote Work Policies - Radha, P; Sayyed, Nasreen; Fathima, Y. (NPRC Journal of Multidisciplinary Research, 2024)
The shift to remote work has fundamentally altered the landscape of cyber security, presenting both challenges and opportunities for organizations. As businesses increasingly rely on digital infrastructure, the need for robust cyber security measures has never been more critical. This paper explores the key cyber security challenges arising from remote work policies, including increased vulnerabilities due to distributed networks, reliance on personal devices, and the heightened risk of social engineering attacks. We analyze how the rapid transition to remote work has outpaced traditional security protocols, often leaving organizations exposed to threats that exploit the gaps in their defenses. With employees working from diverse locations and using various devices, the attack surface has expanded significantly. We also examine the role of employee behavior in cyber security, emphasizing the importance of training and awareness programs to mitigate risks associated with remote work. Furthermore, we discuss best practices for developing comprehensive cyber security strategies tailored to remote work environments. This includes implementing zero-trust security models, enhancing endpoint protection, and fostering a culture of cyber security vigilance among employees. By integrating technology and human factors, organizations can strengthen their defenses against emerging threats. In conclusion, while remote work presents distinct cyber security challenges, it also offers an opportunity for organizations to rethink and innovate their security frameworks. By adopting proactive measures and promoting a security-first mindset, businesses can navigate the complexities of the new normal and safeguard their digital assets effectively. This paper serves as a guide for organizations seeking to enhance their cyber security posture in a world where remote work is likely to remain a significant component of business operations.